Modeling the Process of Adhesion of the Propeller to the Soil Taking into Account the Pitch of the Grousers - Egor G. Khitrov; Ilya S. Dolzhikov; Olga A. Kunitskaya; Varvara P. Druzyanova; Daniil V. Bolotin; Aleksandr V. Andronov (Лесной журнал)
The operational and protective forests of the Russian Federation are characterized by a very wide variety of natural and industrial conditions, including relief and soil ones. The efficiency of forestry machines in various natural and industrial conditions largely depends on their cross-country ability, which is one of the most important performance indicators. A significant amount of theoretical and experimental research by Russian and foreign scientists has been devoted to forecasting the flotation of forestry machines under various operating conditions. An analysis of the work of the predecessors suggests that the known forecast models either do not take into account such an important indicator of forestry machine propellers as the pitch of the grousers, or do not reveal its influence on the propeller adherence to the soil. This work is devoted to the theoretical solution of this issue. Clarifications have been proposed to the estimation of the coefficient of adhesion of the forestry machine propeller to the soil. The mechanism of attenuation of tangential stresses caused by the action of the forestry machine propeller has been described, where attenuation has been described by nonlinear dependencies. An estimate of the coefficient of adhesion obtained with and without taking into account the attenuation of shear deformations along the contact patch has been considered. Calculations have shown that both of these options for numerical estimation of the coefficient of adhesion are consistent and their relative differences are small. An important detail is that as the pitch of the grousers increases, the adhesion estimates without taking into account damping increase monotonically. Thus, for the pitch of the grousers there would be a contradictory recommendation about its maximum possible increase. The results obtained using the proposed formulas, taking into account the attenuation of shear deformations in the soil, make it possible to identify the ranges of pitch variation in which the maximum calculated values of adhesion are noted. For example, with a slip coefficient of 0.05, the maximum is observed at a pitch within 0.15–0.25 m. Thus, the introduction of an expression into the mathematical model that takes into account attenuation makes it possible to reveal a qualitatively different nature of the adhesion function from the pitch of the grousers and mark the optimal range of its values.